2020
DOI: 10.2196/18109
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Primary Care Consultation for Diabetes and Depression Through Digital Medical Interview Assistant Systems: Narrative Review

Abstract: Background Digital medical interview assistant (DMIA) systems, also known as computer-assisted history taking (CAHT) systems, have the potential to improve the quality of care and the medical consultation by exploring more patient-related aspects without time constraints and, therefore, acquiring more and better-quality information prior to the face-to-face consultation. The consultation in primary care is the broadest in terms of the amount of topics to be covered and, at the same time, the short… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Automated medical history taking can improve the quality of care and increase patient satisfaction; patients can document their medical history without any interference or time constraints, and HCPs can prepare for consultations in a time-efficient manner [ 8 , 9 ]. Earlier studies from primary care have suggested many benefits of using automated medical history taking, such as enabling triage prioritization and increasing diagnostic precision [ 10 ]. Potential risks include erroneous information, loss of nonverbal cues, and low digital literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Automated medical history taking can improve the quality of care and increase patient satisfaction; patients can document their medical history without any interference or time constraints, and HCPs can prepare for consultations in a time-efficient manner [ 8 , 9 ]. Earlier studies from primary care have suggested many benefits of using automated medical history taking, such as enabling triage prioritization and increasing diagnostic precision [ 10 ]. Potential risks include erroneous information, loss of nonverbal cues, and low digital literacy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a preliminary interview can reveal the patient's own issues [ 12 ] and that pre-interviews (including via the web) may deepen communication at the initial visit and enhance clinical decision-making. The use of a pre-clinical question prompt list (QPL) in breast cancer genetic counseling has been reported to be useful for assertive communication [ 13 ], and it has been noted that digital interview assistants may have a significant impact on diabetes care, including improved quality of care [ 14 ]. For these reasons, it was thought that prior information improved communication as well as face-to-face clinic time.…”
Section: Discussionmentioning
confidence: 99%
“…(15) A nivel somático se conoce que la depresión y el estrés crónico activan el eje hipotálamo -hipofisario-suprarrenal, estimulando al sistema nervioso simpático, aumentando la agregación plaquetaria y los fenómenos inflamatorios, generando insulinorresistencia, favoreciendo un mal control metabólico. (16,17) Se ha informado que el diagnóstico y tratamiento de la depresión en forma oportuna, mejora el control glucémico y previene o retrasa las complicaciones; (18)(19)(20) a pesar de ello, en los países de bajos y medianos ingresos hay escasez de datos sobre la carga de depresión entre los pacientes con diabetes. (21) Considerando la jerarquía del tema y la gran variabilidad reportadas en estudios publicados a nivel internacional, se realiza este trabajo cuyos objetivos son: conocer la frecuencia de síntomas depresivos y su relación con factores sociodemográficos, control metabólico, tratamiento farmacológico y complicaciones crónicas en una población con DM1 y DM2 que se asiste en una policlínica especializada en hospital de tercer nivel.…”
Section: Introductionunclassified